2019
DOI: 10.1111/sapm.12252
|View full text |Cite
|
Sign up to set email alerts
|

Generalized solitary waves in a finite‐difference Korteweg‐de Vries equation

Abstract: Generalized solitary waves with exponentially small nondecaying far field oscillations have been studied in a range of singularly perturbed differential equations, including higher order Korteweg-de Vries (KdV) equations. Many of these studies used exponential asymptotics to compute the behavior of the oscillations, revealing that they appear in the solution as special curves known as Stokes lines are crossed. Recent studies have identified similar behavior in solutions to difference equations. Motivated by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 41 publications
2
14
0
Order By: Relevance
“…where y 0 (ξ) and z 0 (ξ) take odd and even values of j respectively. There is a significant difference at this stage between the present analysis of the diatomic FPUT lattice, and the analysis of the diatomic Toda lattice from [27]; in the analysis of the Toda lattice, the leading order solution is known exactly, whereas for the FPUT lattice, it is approximated up to O(ǫ 3/2 ). Consequently, we have two small parameters in the system, which introduces an extra source of error into the approximation.…”
Section: Leading-order Series Termsmentioning
confidence: 95%
See 1 more Smart Citation
“…where y 0 (ξ) and z 0 (ξ) take odd and even values of j respectively. There is a significant difference at this stage between the present analysis of the diatomic FPUT lattice, and the analysis of the diatomic Toda lattice from [27]; in the analysis of the Toda lattice, the leading order solution is known exactly, whereas for the FPUT lattice, it is approximated up to O(ǫ 3/2 ). Consequently, we have two small parameters in the system, which introduces an extra source of error into the approximation.…”
Section: Leading-order Series Termsmentioning
confidence: 95%
“…where a dash denotes a derivative with respect to ξ. Before considering the behaviour of this system for small δ, we must determine whether the δ = 0 system contains exponentially small oscillations in the far field due to the discrete nature of the system itself, such as those seen for the discretized Korteweg-de Vries (KdV) equation in [27]. It is straightforward to see that when δ = 0, the governing equations become…”
Section: Diatomic Fput Equationmentioning
confidence: 99%
“…Joshi and Lustri [29] showed that discretization typically results in singularly-perturbed lattice equations and found that discretization changes the behavior of GSWs in lattice Korteweg-de Vries (KdV) equations.…”
Section: Generalized Solitary-wave Solutions and Karpman Equationsmentioning
confidence: 99%
“…Such approximations are valid over very long but nevertheless finite time intervals; the erosion is so subtle during the period of good approximation that it falls within the natural error bounds. Moreover, radiating solitary waves very often occur in problems where the construction of genuinely localized solitary waves fails and what is found instead are generalized solitary waves (also known as a nanopterons) [2,1,31,10,7,17,8,23,19,20,24]. These traveling wave solutions are asymptotic at spatial infinity to very small amplitude co-propagating periodic waves and are consequently of infinite energy, further evidence that the dynamics of finite energy solitary wave-like solutions is subtle.…”
Section: Introductionmentioning
confidence: 99%